Examining the consistence of futures margin levels using bivariate extreme value copulas - X. Gong (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This study examines the consistence of the futures margin levels of different commodities and combinations in the CME group by Extreme Value Copula (EVC).We find that if we ignore the co-movements of the commodities, the margins become consistent with each other, and the margin violation rates hover around 0.5%. However, if we consider the co-movement of the related commodities using EVC, the margin levels are found to be not consistent anymore, especially in the combinations of strongly related commodities which are in the same category. Therefore, we suggest that the CME group should try to harmonize the margins policy with respect to the dependence between the futures in the future.